The phenomenon of glass ceiling toward female employees in banking industry in Sabah case study Bank Rakyat Kota Kinabalu / Syazwani Sulaiman, Marliana Bakri and Zamzuri Hassan - Sulaiman, Syazwani; Bakri, Marliana; Hassan, Zamzuri (2013)
Glass ceiling as we know refers to the barrier faced by female employee in her career development at the existence organization. This phenomenon occurs when the potential of female employee did not be given an equal opportunity at the top management to shows the ability to growth the organization business in high level and to achieved goal. This phenomenon is mostly happen in large organization in western countries. The barriers for female employee to be promoted in highest position in the organization can be seen in term of gender, family commitment, qualification, and etc. Bank Rakyat is one of the largest banking industries in Malaysia and provided business like others bankers such as saving, credit, loan and others. Bank Rakyat establish under Cooperative Ordinance 1948. In Sabah, Bank Rakyat has 13 branches around the state and controlled by the Regional Office in Sembulan, Kota Kinabalu. The research created and analyzes the existence of glass ceiling at Bank Rakyat in the area of promotion from lower level into highest level such from clerk position to officer and also from officer to manager position in each branch. The survey conducted using interview and distribute questionnaire among branches at Kota Kinabalu (nemaly Regional Office), Likas, Penampang and Putatan. The interview session has been conducted at Beaufort Branch in order to get an extra data to analyze which is there is the first female in Sabahan was appointed as a Branch Manager.